Effect of iron doping on the structural and optical properties of CeO2 films - Channei D. (2017)
Â© 2016, Springer Science+Business Media New York. Abstract: Undoped and Fe-doped CeO 2 thin films were fabricated by spin coating on F-doped tin oxide glass substrates followed by annealing at 500Â Â°C for 15Â h. The concentration of the dopant was varied from 2 to 10Â % iron by weight (metal basic). Glancing angle X-ray diffraction and laser Raman microspectroscopy indicated that the films consisted only of CeO 2 without any impurity phases of Fe x O y . The thickness of the films was determined by dual-beam focused ion beam milling to be ~150Â nm for undoped film, while Fe-doped CeO 2 films have thickness of ~200Â nm for all dopant samples. The transmission spectra from UV–visible spectrophotometry showed a redshift of the absorption edge of the doped films, and the optical indirect band gap of the films decreased from 3.48 to 3.20Â eV with increasing dopant concentration. Furthermore, the results have been proposed in the diagram of electron–hole trapping. Graphical Abstract: [Figure not available: see fulltext.]